2019
DOI: 10.1002/jmri.27008
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric MRI‐Based Radiomics for Prostate Cancer Screening With PSA in 4–10 ng/mL to Reduce Unnecessary Biopsies

Abstract: BackgroundWhether men with a prostate‐specific antigen (PSA) level of 4–10 ng/mL should be recommended for a biopsy is clinically challenging.PurposeTo develop and validate a radiomics model based on multiparametric MRI (mp‐MRI) in patients with PSA levels of 4–10 ng/mL to predict prostate cancer (PCa) preoperatively and reduce unnecessary biopsies.Study TypeRetrospective.SubjectsIn all, 199 patients with PSA levels of 4–10 ng/mL.Field Strength/Sequence3T, T2‐weighted, diffusion‐weighted, and dynamic contrast‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 28 publications
2
62
0
Order By: Relevance
“…Radiomics is defined as high-throughput extraction of mineable, quantitative, and highdimensional medical imaging features using machine learning (13,14). Recently, the emerging radiomics technique has been widely applied in PCa research, which was reported to have added value in PCa detection, aggressiveness assessment, and survival analysis (15)(16)(17)(18)(19)(20). One of the explanations of radiomics' superiority maybe that radiomics could provide more information about the lesion which might be correlated with the intratumor heterogeneity (13).…”
Section: Introductionmentioning
confidence: 99%
“…Radiomics is defined as high-throughput extraction of mineable, quantitative, and highdimensional medical imaging features using machine learning (13,14). Recently, the emerging radiomics technique has been widely applied in PCa research, which was reported to have added value in PCa detection, aggressiveness assessment, and survival analysis (15)(16)(17)(18)(19)(20). One of the explanations of radiomics' superiority maybe that radiomics could provide more information about the lesion which might be correlated with the intratumor heterogeneity (13).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Wibmer A. et al [ 36 ] showed promising results of Radiomics in PCa detection and Gleason Score (GS) assessment on mpMRI, in particular Gleason Score (GS) was significantly associated with higher values of Entropy (GS 6 vs. 7: p = 0.0225; 6 vs. >7: p = 0.0069) and lower values of energy (GS 6 vs. 7: p = 0.0116, 6 vs. >7: p = 0.0039) derived from ADC maps. Furthermore, Qi Y. et al [ 37 ] created a radiomic model by using a random forest classifier, based on 2104 features extracted from MRI sequences. The combined model (radiological and clinical data) returned AUC values of 0.956 and 0.933 on the test ( n = 133) and validation ( n = 66) population, respectively, making it an additional potential tool for the clinicians in treatment decision-making.…”
Section: Prostate Cancermentioning
confidence: 99%
“…Those studies [44][45][46][47][48][49][50][51][52][53][54] employed multiple lesions for each patient enrolled in the study. Subgroup 2 gathered those studies [55][56][57][58][59] that enrolled two distinct groups (PCa and controls) and employed a patient-based ML approach. The heterogeneity in the subgroups was greater than 70% (subgroup 1: P<.001, subgroup 2: P=.002).…”
Section: Subgroup Analysismentioning
confidence: 99%
“…High heterogeneity may be due to the different cross-validation techniques used (eg, bootstrapping [16,40,52], Monte Carlo cross-validation [17]) or the choice of number of folders used in cross-validation methods; if an external data set was used [52,60,61,63], differences in the study protocols may have increased the bias among studies. Moreover, few studies in radiomic [50,53,57,59] and genomic [17,67] analysis employed both cross-validation and external testing. Studies employing no validation showed very low heterogeneity (only 2 studies in radiomic analysis), which may be due to the absence of other confounding variables, and high performances may be due to overfitting problems.…”
Section: Principal Findingsmentioning
confidence: 99%
See 1 more Smart Citation